2013
DOI: 10.1088/0953-8984/25/5/055303
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures of Sr2+doped BiFeO3multifunctional ceramics with tunable photoluminescence and magnetic properties

Abstract: Careful tuning of formation (calcination) temperature of Sr(2+) doped BiFeO(3) multiferroic ceramics results in tailorable particle morphologies ranging from spherical to pillar-like. Based on the minimization of Gibb's free energy approach, the dominant homogeneous mechanism for particle growth is suggested. The chemical substitution of a trivalent ion (Bi(3+)) by a divalent ion (Sr(2+)) causes the transformation of certain fraction of Fe(3+) to Fe(4+) and/or the appearance of oxygen vacancies. This has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…3C shows the PL spectra of P-BFO and T/P-BFO nanocomposites with the excitation wavelength of 325 nm. It is observed that the P-BFO and T/P-BFO nanocomposites exhibit strong PL signals (blue emission) at the wavelength range from 350 to 525 nm, which is mainly attributed to the electronic transitions from the conduction band of BFO to its valance band [30,31]. Generally speaking, lower the PL signal, lower the charge recombination rate and higher the separation efficiency.…”
Section: Photogenerated Charge Transfer and Separationmentioning
confidence: 99%
“…3C shows the PL spectra of P-BFO and T/P-BFO nanocomposites with the excitation wavelength of 325 nm. It is observed that the P-BFO and T/P-BFO nanocomposites exhibit strong PL signals (blue emission) at the wavelength range from 350 to 525 nm, which is mainly attributed to the electronic transitions from the conduction band of BFO to its valance band [30,31]. Generally speaking, lower the PL signal, lower the charge recombination rate and higher the separation efficiency.…”
Section: Photogenerated Charge Transfer and Separationmentioning
confidence: 99%
“…Magnetization hysteresis loops of (Bi 0.95 Sr 0.05 )FeO 3 À δ (BFO5Sr) ceramic show a weak ferromagnetism due to straightening of the Fe-O-Fe bond angle [10]. X-ray photoelectron spectroscopy and neutron diffraction of (Bi 1 À x Sr x )FeO 3 À δ (x¼ 0.0-0.5) ceramics synthesized using a modified gel-combustion, suggest that the Bi 3 þ -Sr 2 þ substitution causes Fe 3 þ -Fe 4 þ transformation and oxygen vacancies [10]. Structures of (Bi 1 À x Sr x )FeO 3 À δ (x¼ 0.0-0.5) remain in the rhombohedral R3c space group and rhombohedral distortion decreases with increasing Sr 2 þ content [10].…”
Section: Introductionmentioning
confidence: 98%
“…X-ray photoelectron spectroscopy and neutron diffraction of (Bi 1 À x Sr x )FeO 3 À δ (x¼ 0.0-0.5) ceramics synthesized using a modified gel-combustion, suggest that the Bi 3 þ -Sr 2 þ substitution causes Fe 3 þ -Fe 4 þ transformation and oxygen vacancies [10]. Structures of (Bi 1 À x Sr x )FeO 3 À δ (x¼ 0.0-0.5) remain in the rhombohedral R3c space group and rhombohedral distortion decreases with increasing Sr 2 þ content [10]. It was reported that Sr doping can stabilize the BFO perovskite structure [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much attention has been paid toward BFO-based single-phase multiferroic materials due to their potential applications in transducers, sensors, memories, spintronics, and owing to their interesting physics background [3]. Therefore, BFO-based multiferroics have been studied widely in ceramics as well as in thin film-related aspects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%